2014
DOI: 10.4103/2141-9248.129035
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction and its influential factors in dental academic members in Tehran, Iran

Abstract: Background:Assessment of job satisfaction of the faculty members and its underlying factors may increase career fulfillment and raise the educational and research productivity, leading to higher quality of dental services at the community level, ultimately improving public oral health status.Aim:This study assessed job satisfaction and its influential factors in dental academic members in Tehran.Subjects and Methods:The job satisfaction level of 203 faculty members was assessed using a Likert scale questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 17 publications
3
15
1
Order By: Relevance
“…Dentistry is considered to be one of the most stressful professions 3 4 5 with the overall job satisfaction varying between countries. 10 11 12 13 14 15 16 17 18 19 This study was conducted to assess the overall job satisfaction among working dentists in the UAE and to assess the effect of sociodemographic factors and work environment factors on their level of satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dentistry is considered to be one of the most stressful professions 3 4 5 with the overall job satisfaction varying between countries. 10 11 12 13 14 15 16 17 18 19 This study was conducted to assess the overall job satisfaction among working dentists in the UAE and to assess the effect of sociodemographic factors and work environment factors on their level of satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…1 5 11 12 The lowest levels of job satisfaction were reported in Iran, where the mean satisfaction scores were relatively low (1.5 out of 5) which indicates that dentists in Iran may find their jobs to be stressful. 13…”
Section: Introductionmentioning
confidence: 99%
“…The importance of remuneration has also been discussed in other studies. 27 28 A study conducted at three teaching hospitals in Karachi showed that most doctors were not satisfied with their work and the lowest satisfaction was reported for wages and benefits. 27 The health system reforms in China in 2009 had an unintended impact on the income of healthcare staff.…”
Section: Discussionmentioning
confidence: 99%
“…Facilities available on campus, salary packages, annual incentives offered, and promotion and tenure procedures are firmly believed to account for faculty dissatisfaction (Seraj et al, 2014). Faculty at Avalon perceive that effective salary packages (table 2; question 5; mean is 3.86 and median and mode are 4) and annual incentives and hikes (table 2; question 6; mean is 3.50, median and mode are 4) are considered as important factors in retaining the faculty members in higher education.…”
Section: Discussionmentioning
confidence: 99%